2022
DOI: 10.1007/s12072-022-10461-1
|View full text |Cite
|
Sign up to set email alerts
|

Liver fibrosis is associated with impaired bone mineralization and microstructure in obese individuals with non-alcoholic fatty liver disease

Abstract: Background and purposeChronic liver diseases are associated with increased bone fracture risk, mostly in end-stage disease and cirrhosis; besides, data in non-alcoholic fatty liver disease (NAFLD) are limited. Aims of this study was to investigate bone mineralization and microstructure in obese individuals with NAFLD in relation to the estimated liver brosis. MethodsWe analyzed data from 1872 obese individuals (44.6 ± 14.1 years, M/F: 389/1483; BMI: 38.3 ± 5.3 kg/m 2 ) referring to the Endocrinology outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A previous study by Cherukuri et al, 2021 reported strong association between low body weight and osteoporosis in the general population (Cherukuri et al, 2021). A study by Barchetta et al,2022 reported that low urinary creatinine levels indicate low muscle mass and are correlated with low BMD in chronic liver disease (Barchetta et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…A previous study by Cherukuri et al, 2021 reported strong association between low body weight and osteoporosis in the general population (Cherukuri et al, 2021). A study by Barchetta et al,2022 reported that low urinary creatinine levels indicate low muscle mass and are correlated with low BMD in chronic liver disease (Barchetta et al, 2022).…”
Section: Discussionmentioning
confidence: 96%
“…Importantly, the combined use of diverse MR analysis methods and multiple sensitivity analysis methods bolstered the reliability of the results. Additionally, musculoskeletal disorders are associated with various broadly defined cirrhosis [ 70 , 71 ] and diverse types of cancer [ 72 , 73 ]. To mitigate potential bias arising from these associations, the controls for liver cirrhosis and HCC in this study were defined to exclude broadly defined cirrhosis and all types of cancer, respectively, which ensured a higher degree of accuracy in the results of the causal analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a cross-sectional study from 1,872 obese individuals in Rome, Italy, Barchetta et al. found that higher FIB-4 score, an index of liver fibrosis, was independently associated with lower BMD and increased risk of osteopenia/osteoporosis ( 20 ). Moreover, available evidence about the associations of liver fibrosis with BMD and the risk of osteopenia/osteoporosis for T2DM patients was quite limited.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies based on cross-sectional analyses of the 2017–2018 cycle of NHANES in the US population older than 50 years found similar results that liver steatosis and fibrosis are not independently associated with osteopenia or osteoporosis although patients with MAFLD showed increased BMD than their controls ( 17 19 ). However, a cross-sectional study from 1,872 obese individuals in Rome, Italy found that higher Fibrosis-4 (FIB-4) score, an index of liver fibrosis, was significantly associated with lower BMD and increased risk of osteopenia/osteoporosis ( 20 ). Yet, there was no evidence available about the associations of MAFLD and liver fibrosis with BMD and osteopenia/osteoporosis in patients with T2DM, although MAFLD and osteoporosis share with T2DM some common pathophysiological mechanisms, such as insulin resistance, hyperinsulinemia, pro-inflammatory state of liver and adipose, enhanced lipotoxicity, and excessive reactive oxidative stress ( 7 , 8 , 14 ).…”
Section: Introductionmentioning
confidence: 99%